Irradiance data analysis - Kwok, Ervin (2019)
In Singapore, the tropical climate has high variability in solar irradiance. The irradiance is often scattered by cloud cover in Singapore’s tropical climate, which causes variations in the solar power output. The report ahead compares the performance of 2 different power inverters – SMA and SolarEdge, installed on the rooftop of Nanyang Technological University, to convert the output of PV panels from DC to AC. One of the inverters (the SolarEdge inverter) has individual module optimizers (with maximum power point tracking (MPPT) at each module), while the other has a global MPPT system. Evaluation of the two inverters was performed by categorizing the daily solar irradiation based on the global horizontal output of an irradiance sensor. The data were grouped into 5 classifications based on the irradiance variability characteristic, that is, High with little variability, High with variability, High variability, Low with variability, and Low with little variability. The accumulated power output for each inverter was calculated for each of the five classifications and compared. Results show that the SMA inverter with 2 MPPTs built-in is the best performing inverter, with an even better performance in high variability situations. It indicates that module optimizer seems to be really effective against variability.